“Siaga Gizi, Siaga Bencana”: Penguatan Kesiapsiagaan Masyarakat melalui Edukasi Gizi Darurat di Desa Hutadaa Kecamatan Talaga Jaya - Sulaiman Putra Nagaring; uhriana K Yusuf; Sitty Fadhilla Fitrianty Lahay; Riska Nuryana; Jesica Mulyadi (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
Disaster situations can disrupt food access and increase the risk of nutritional problems, especially among vulnerable groups such as children, pregnant women, breastfeeding mothers, older adults, and individuals with chronic diseases. This community service activity aimed to strengthen community preparedness through emergency nutrition education in Hutadaa Village, Talaga Jaya District, Gorontalo Regency. The activity used an educational and participatory approach through PowerPoint presentations, educational videos, interactive discussions, and question-and-answer sessions. The results showed that participants were enthusiastic and actively involved, particularly in discussions about nutritious emergency foods and priority groups during disasters. The use of visual media and interactive discussion helped participants understand that nutrition fulfillment during disasters should consider not only food availability but also nutritional quality and household preparedness. This activity concludes that community-based emergency nutrition education can serve as a promotive and preventive strategy to improve community preparedness for nutritional risks during disasters.